LITERALNESS IN TRANSLATING TEXTS FROM ENGLISH INTO INDONESIAN - Zulprianto Zulprianto (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
This article seeks to describe literalness in translating English texts into Indonesian. The foci of literalness observed in this study are of word order and of word choice. Data are translations of twelve respondents asked to translate a given English text, which is approximately 500 words in length, into Indonesian. The respondents are senior students of English Department Students of Andalas University. Therefore, there are twelve comparable texts collected. During the translation process, the respondents were given a plenty of time and were also allowed to use any kinds of translation aids such as dictionary, encyclopedia, etc, but disallowed to use machine translation without human editor. The analysis, by making comparison between the English source text (ST) and the twelve translated texts (TT), shows that the respondents tend to apply literal methods or strategies in their translations especially in terms of word order or syntactical constructions, to be more general. These tendencies in general do not necessarily produce inadequate translations, but to some degree, may produce less natural target texts. In addition, the respondents make some considerable literalness somehow leading to inaccuracy in choosing the equivalence for several words/phrases of the source text. The inaccuracy they make occasionally end them up with producing poor translations. The output obtained from this research is worth noting in the effort to improve translation quality when it is used either as an alternative method of foreign language teaching or language testing.